2015
DOI: 10.1161/hypertensionaha.114.04852
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Continuous Positive Airway Pressure Treatment on Clinic and Ambulatory Blood Pressures in Patients With Obstructive Sleep Apnea and Resistant Hypertension

Abstract: Abstract-The effect of continuous positive airway pressure (CPAP) on blood pressures (BPs) in patients with resistant hypertension and obstructive sleep apnea is not established. We aimed to evaluate it in a randomized controlled clinical trial, with blinded assessment of outcomes. Four hundred thirty-four resistant hypertensive patients were screened and 117 patients with moderate/severe obstructive sleep apnea, defined by an apnea-hypopnea index ≥15 per hour, were randomized to 6-month CPAP treatment (57 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
74
0
11

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(88 citation statements)
references
References 32 publications
3
74
0
11
Order By: Relevance
“…However, the beneficial effect of CPAP on BP in patients with OSA and resistant hypertension is inconsistent. [16][17][18][19][20] Therefore, we conducted a metaanalysis to evaluate the efficacy of CPAP in patients with OSA and resistant hypertension.…”
mentioning
confidence: 99%
“…However, the beneficial effect of CPAP on BP in patients with OSA and resistant hypertension is inconsistent. [16][17][18][19][20] Therefore, we conducted a metaanalysis to evaluate the efficacy of CPAP in patients with OSA and resistant hypertension.…”
mentioning
confidence: 99%
“…[16][17][18][19] Randomized clinical trials have demonstrated modest antihypertensive benefits of treatment of SDB with CPAP, with mild reductions in BP of 3 to 5 mm Hg 20,21 compared with more substantive reductions in RHTN, namely 7 to 10 mm Hg. 22 Notwithstanding the vast interventional trial data published on SDB and HTN, relatively fewer randomized studies [23][24][25] have investigated the effect of CPAP on control of BP in patients with OSA and RHTN, and none have examined the effect of CPAP in real-world clinical practice settings. 22,26,27 The limited data available in the "real-world" clinical practice setting suggests a reduction in mean arterial pressure (MAP) in a small sample of patients with resistant hypertension, and a negligible effect on hypertensive patients with controlled BP.…”
mentioning
confidence: 99%
“…18 However, not all studies showed similar results; in recent RCTs 3-6 months of CPAP had no impact on BP in patients with moderate to severe OSA and resistant hypertension. 19,20 Furthermore, in an 8-week RCT with a crossover design, both CPAP and valsartan resulted in a significant reduction in mean 24-hour BP but valsartan was superior to CPAP (−7.0 mm Hg, 95 % CI −10.9 to −3.1 mm Hg; p<0.001). 21 The impact of CPAP on incident hypertension was assessed in one RCT, in which 723 patients with AHI ≥20 and ESS ≤10 were randomised to CPAP versus no CPAP.…”
Section: Impact Of Obstructive Sleep Apnoea Treatmentmentioning
confidence: 98%